Resolving the age of the Haughton impact structure using coupled 40Ar/39Ar and U-Pb geochronology. (1st July 2021) - Erickson, Timmons M.; Kirkland, Christopher L.; Jourdan, Fred; Schmieder, Martin; Hartnady, Michael I.H.; Cox, Morgan A.; Timms, Nicholas E.
Abstract: The Haughton Dome located on Devon Island, in the Canadian Archipelago represents a well-preserved, moderate-sized, complex impact crater. Previous age constraints for the 24 km-diameter impact structure have ranged from ca. 21 Ma to ca. 39 Ma. Herein, we present a coordinated microstructural and in situ U-Pb study of zircon and monazite coupled with 40 Ar/ 39 Ar laser step heating of shock-melted K-feldspar clasts from shock metamorphosed gneissic fragments collected from the allochthonous impact breccia at Haughton. Moderately shocked zircon and monazite grains yield an age distribution consistent with an Archean protolith metamorphosed at ca. 1.9 Ga, whereas shock recrystallized zircon and monazite yield a lower intercept age of 31.8 ± 1.7 Ma (n = 48, MSWD = 0.58, P = 0.99). Four inverse isochron 40 Ar/ 39 Ar ages of shocked feldspar clasts yield a weighted mean age of 31.04 ± 0.37 Ma (MSWD = 0.98, P = 0.40), within uncertainty of the U-Pb lower concordia intercept. Ar diffusion modelling supports the interpretation of the impact age and helps resolve impact-driven age resetting. These results highlight the power of coupling multiple geochronologic techniques for determining impact ages, especially from targets with complex geologic histories. Furthermore, they resolve previous discrepancies in the age of the Haughton Dome and the interpretation of the post impact stratigraphy of the crater fill.